2016
DOI: 10.1590/0004-282x20160017
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular disorders in fibromyalgia patients: are there different pain onset?

Abstract: Objective To identify temporomandibular disorders (TMD) symptoms in two groups of fibromyalgia patients according to the temporal relation between the onset of facial pain (FP) and generalized body pain (GBP). Cross-sectional study design: Fifty-three consecutive women with fibromyalgia and FP were stratified according to the onset of orofacial pain: Group-A (mean age 47.30 ± 14.20 years old), onset of FP preceded GBP; Group-B (mean age 51.33 ± 11.03 years old), the FP started concomitant or after GBP. Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
(30 reference statements)
0
12
0
1
Order By: Relevance
“…In terms of genetics, Yigit et al (12) demonstrated an association between IL-4 gene polymorphism and risk of FMS development. Fujarra et al (46) evaluated TMJ disorder symptoms in FMS patients and found that FMS patients were suffering TMJ symptoms with muscle disorders, disc displacement and myofascial pain with limited mouth opening. Oral manifestations of FMS, such as TMJ dysfunction, xerostomia, hyposalivation and burning mouth syndrome have also been suggested (34,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of genetics, Yigit et al (12) demonstrated an association between IL-4 gene polymorphism and risk of FMS development. Fujarra et al (46) evaluated TMJ disorder symptoms in FMS patients and found that FMS patients were suffering TMJ symptoms with muscle disorders, disc displacement and myofascial pain with limited mouth opening. Oral manifestations of FMS, such as TMJ dysfunction, xerostomia, hyposalivation and burning mouth syndrome have also been suggested (34,47).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, none of the patients reported xerostomia, hypo-salivation or burning mouth in their dental and medical history. It might be reasonable to expect these problems in FMS patients as all these symptoms are somehow related to musculoskeletal malfunctions (34,46,48). However, studies on oral manifestations of FMS or orofacial complaints of FMS patients are limited (49).…”
Section: Discussionmentioning
confidence: 99%
“…Fujarra et al, 2016 [31] All patients showed TMD and muscle disorders, with limited opening and TMJ disc displacement. According to the authors, Myofascial pain could be associated with mouth opening limitation (p = 0.038); right disc displacement with reduction (p = 0.012) and jaw stiffness (p = 0.004) were predominant in the facial pain group.…”
Section: Cummiford Et Al 2016 [30]mentioning
confidence: 97%
“…This transcranial stimulation may produce analgesia on TMD too. Fujarra et al [31] showed oro-facial symptoms of FM patients, evaluating joint and muscle disorders with associated pain. Robinson et al [32] evaluated differences between TMD and CFS, CFS is a syndrome associated with hypersensitivity of the CNS, and it is a similar condition to FM.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Se tomó la medición para comprobar la intensidad del dolor en tres momentos distintos tal y como aconseja la literatura (258). Por tanto, la EVA se utilizó en el presente estudio para medir la percepción dolorosa recibida por el paciente, si bien no se utilizó para valorar la efectividad del tratamiento.…”
Section: Dolor Escala Analógica Visualunclassified